Selection of the best E-Wallet in Klang Valley, Malaysia: an application of the analytic hierarchy process - Islam, Rafikul; Amaloo, Rajan (World Academy of Islamic Management, 2023)
Parties conducting electronic businesses usually do not meet face-to-face, nor do they exchange currency or hard copies of documents hand-to-hand. When companies enter into electronic commerce transactions, choosing an electronic payment (or E-Wallet) system that will work well is a major issue. In this paper, after examining different E-Wallet systems in Klang Valley, Malaysia, assessment criteria are identified based on previous research and interviewing experts. Then, using Analytic Hierarchy Process (AHP), various E-Wallets in Klang Valley are prioritized. Results show that Samsung Pay is the most preferred E-Wallet system, followed by Lazada e-Wallet and Boost. The findings of this research are intended to be useful for both academic researchers and companies planning to adopt or to improve an electronic payment system.